Relasi Alam Pikiran Matematika dan Realitas: Telaah Pemikiran Filsafat Matematika The Liang Gie - Rilliandi Arindra Putawa (Undiksha, 2022)
The relation between mathematics and reality is a philosophical problem that needs more attention, considering that mathematics and philosophy, especially ontology, are two fields that discuss reality at a higher level than other sciences, such as physics. The Liang Gie is one of the few philosophical figures in Indonesia who pays more attention to philosophical problems in the field of mathematics, through three parts of his work in the field of philosophy of mathematics. One of the topics discussed in his work is related to mathematical ontology. This study aims to explore the main points of The Liang Gie's thoughts, which are related to mathematical ontology, especially related to the relationship between the mathematical mind and reality. This article is a literature study on the thoughts of The Liang Gie's mathematical ontology. By using qualitative research methods in the field of philosophy, the data obtained from the literature study will be processed to obtain a philosophical knowledge that has implications for real life. There are three assumptions that can be concluded through the discussion of this research. First, some figures think that mathematics can stand alone with its own existence without having to relate to objects in the real world. Second, there is also an assumption that mathematics is considered responsible for everything in the universe or even mathematics is considered as the universe itself. Third, inmany ways mathematics has a strong relationship with empirical phenomena, especially with regard to the measurement process. These three conclusions can then be linked to themathematical philosophy approach, such as Platonism, Absolutism, and Fallibilism.